2005
DOI: 10.1111/j.1460-9568.2005.04215.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of substantia nigra pars reticulata neurons during smooth pursuit eye movements in monkeys

Abstract: Nuclei within the basal ganglia (BG), in particular the substantia nigra pars reticulata (SNr), subthalamic nucleus (STN) and caudate nucleus, are known to be involved in the generation of rapid or saccadic eye movements. Neurons in the SNr are active tonically and generally show a pause, but also increase, in discharge rate, for the appearance of visual stimuli and the generation of saccades. Recent experimental results in oculomotor regions of the brainstem reveal overlap in the neuronal pathways used for sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 61 publications
5
50
0
Order By: Relevance
“…Cholinergic stimulation of superior colliculus leads to improved initiation of eye movements (Aizawa et al, 1999), whereas electrical stimulation of substantia nigra operates bidirectionally and either suppresses or enhances pursuit movement (Basso et al, 2005). While these structures are potential action sites of the present pharmacological challenge, on the basis of our findings their involvement in the observed drug effect remains suggestive.…”
Section: Accepted M Manuscriptsupporting
confidence: 54%
“…Cholinergic stimulation of superior colliculus leads to improved initiation of eye movements (Aizawa et al, 1999), whereas electrical stimulation of substantia nigra operates bidirectionally and either suppresses or enhances pursuit movement (Basso et al, 2005). While these structures are potential action sites of the present pharmacological challenge, on the basis of our findings their involvement in the observed drug effect remains suggestive.…”
Section: Accepted M Manuscriptsupporting
confidence: 54%
“…The firing rate of many of these neurons was modulated during pursuit in opposite directions, and neuronal activity often persisted even after target motion, suggesting that the neuronal activity was strictly related neither to the direction nor to the speed of pursuit. Similar to neurons in the SNr [12] and in the thalamus [15], most pursuit-related neurons in the GP also modulated firing during saccades to a stationary target. Importantly, however, the firing modulation during pursuit was present even in the absence of catch up saccades.…”
Section: Discussionmentioning
confidence: 87%
“…Because both neurons exhibited firing modulation for trials without early saccade (raster lines with left bracket), the activity during pursuit was not solely due to the occurrence of catch up saccades. Although the neuronal modulation during pursuit was observed even when catch up saccades were absent, most pursuit-related neurons in the GP also responded to saccades to a stationary target, like neurons in the SNr [12] and in the thalamus [15]. When neuronal activity during saccades of 16° was examined, 83% neurons (n = 33/38 increase-type neurons; n = 32/40 decrease-type neurons) exhibited clear firing modulation.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Several lines of evidence suggested that the SNr plays critical roles in the control of saccadic eye movements (Handel and Glimcher, 1999;Basso and Wurtz, 2002;Bayer et al, 2004;Basso et al, 2005;Basso and Liu, 2007). One of the interesting observations reported by Basso and Liu (2007) is that electrical stimulation of the SNr both reduced and prolonged saccade latency.…”
Section: Functional Implicationsmentioning
confidence: 89%